Knowledge and awareness of school teachers regarding emergency management of dental trauma in school children of Navi Mumbai - Farhin A Katge; Devendra P Patil; Pooja J Khakhar; Manohar S Poojari; Paloni B Koticha (Wolters Kluwer Medknow Publications, 2021)
Context: Dental trauma is a serious oral health problem that can impair function and aesthetics, which affects the overall quality of life in children. Aims: The aim of the present study was to identify the level of knowledge and awareness of school teachers regarding emergency management of dental trauma in school children of Navi Mumbai. The second objective was to correlate it with demographic characteristics and evaluate the need for oral health education programs for teachers. Settings and Design: The present study is a cross-sectional survey and involved the completion of a self-administered anonymous questionnaire by teachers. Materials and Methods: A total of 559 school teachers of primary and secondary sections completed the questionnaire comprising 19 questions. These included demographic data, knowledge regarding teeth most frequently affected by trauma, immediate action to be taken, awareness about storage media and the use of mouth guards. The questionnaire also assessed the willingness of teachers to participate in future training programs on dental trauma management. Data were statistically analysed using Chi-square test for any correlation. Results: Among 559 school teachers who completed the questionnaire, 75.3% were females and 24.7% were males. Merely 6.6% of them agreed to have received prior training in dental trauma management. The majority of teachers (87.5%) were willing to attend training programs on dental trauma management. Conclusions: The knowledge and awareness of school teachers about dental trauma management and storage media for avulsed teeth is poor. Overall, they have a fair knowledge of dental trauma management in school children.